ANALISIS PERBANDINGAN UNJUK KERJA PEMANAS AIR TENAGA SURYA TIPE PLAT DATAR DENGAN SISTEM SINGLE DAN DOUBLE CUTOFF - Ivan Budiman; I Made Kartika; Abrar Riza (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: Warm water is needed by human being to take a bath, wash their clothes, their dishes etc. By the photothermal conversion, the solar energy can be used to heat the water. Flat solar collector is a tool which is used to capture energy of the sun radiation then convert it into heat to heat up water in collector’s pipes. The number of glass cover used effects the performance and efficiency of the collector. From this research, it is found that the efficiency of the collector is better when the cover used are two glasses than one glasses. The temperature difference of incoming and outgoing water in the collector using two glasses 15 ̊C higher than that of one glass.